Management in Non-Profit Organizations Ikatan Mahasiswa Kota Batu (IMAKOBA) - Arif, Moh. Erfan (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This study aims to improve the managerial skills of administrators and members of the Batu City Student Association (IMAKOBA), a non-profit organization facing operational challenges. Addressing these issues is crucial to enhancing the organization's effectiveness and impact. Method: The study involved a management training program using lectures, role-playing, and discussions to enhance participants' leadership, planning, and control skills. Practical Applications: The findings provide practical strategies to improve management in non-profit organizations, enhancing their effectiveness and sustainability, especially in youth-driven initiatives. Conclusion: The training improved key skills in leadership and planning, offering valuable insights into resolving managerial challenges and optimizing non-profit organizations' operations.